2015
DOI: 10.1002/mus.24697
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in myasthenia gravis: A nationwide population–based follow‐up study in Denmark

Abstract: MG diagnosis is still associated with increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 28 publications
2
34
0
7
Order By: Relevance
“…Age and gender impacts on myasthenia gravis mortality have been controversial [22,23,31,32]. In our study, we found the incidence of postoperative complications lower in male and elderly patients than in females and other age groups.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Age and gender impacts on myasthenia gravis mortality have been controversial [22,23,31,32]. In our study, we found the incidence of postoperative complications lower in male and elderly patients than in females and other age groups.…”
Section: Discussionsupporting
confidence: 47%
“…In our study, we found the incidence of postoperative complications lower in male and elderly patients than in females and other age groups. Similarly, a 2015 nationwide population-based study in Denmark enrolled 702 AChR-Ab-seropositive myasthenia gravis patients and found myasthenia gravis mortality rates were higher in women and early-onset myasthenia gravis, perhaps due to increased frequency of combined autoimmune disorders and thymoma in these patients [22,31,32]. Although mortality and postoperative complications differ, these groups of patients could be followed with greater care after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos signos, explorados en forma aislada, desvían la atención y pueden confundirse con crisis asmática (27,28) por lo cual se debe realizar anamnesis exahustivas. El electromiograma de fibra única (SFEMG), es un examen útil para diagnosticar la enfermedad, y tiene alta especificidad y sensibilidad en pacientes con anticuerpos positivos, la prueba con inhibidores de la colinesterasa como el Edrofonio tiene alta sensibilidad en pacientes con anticuerpos a AchR, no observándose lo mismo en pacientes con anti-Musk (1) (7,8), por las condiciones al ingreso de la paciente y teniendo los resultados de anticuerpos a AchR positivos , no se realizaron estas pruebas en la paciente; pero si utilizamos la prueba del hielo que fue positiva, ésta se trata de una prueba simple y eficaz, que consiste en colocar un recipiente de hielo sobre los párpados cerrados del paciente durante un período de 2 minutos para ptosis y 5 minutos para oftalmoparesia . Los déficits de motilidad ocular y la apertura palpebral deben medirse antes y después de la prueba.…”
Section: Discussionunclassified
“…The reported incidence of MG has markedly varied across epidemiological studies, and the pooled annual incidence of MG was calculated to be 5.3 per million persons based on 55 population-based epidemiological studies [3]. Notably, MG diagnosis is associated with increased risk of mortality [4, 5]. …”
Section: Introductionmentioning
confidence: 99%